Cultural Trauma in Wagle’s ‘Palpasa Café’ - Kattel, Achut Raj (Medha: A Multidisciplinary Journal, 2023)
This research article focuses in the area of Wagle’s ‘Palpasa Café’ in the background of Maoist’s insurgency in Nepal. Such a study is significant in order to diagnose the society that faced dreadful events and envision the trouble and trauma people faced during the insurgency. The research method adopted in this article is cultural trauma defined by Jeffrey C. Alexander. The major findings of the present article are characters face dreadful events in the novel ’Palpasa Café’ and it frightens them so much that they are anxious of their future identity and security. ‘Palpasa Café’ has the setting of war, and it shows the terror felt both in city and village. The study's main conclusions are ‘Palpasa Café’ is a novel of cultural trauma and it presents a large number of people affected by the horrendous event.